2015
DOI: 10.5897/ajmr2015.7580
|View full text |Cite
|
Sign up to set email alerts
|

Use of thermal imaging for the early detection of signs of disease in pigs challenged orally with Salmonella typhimurium and Escherichia coli

Abstract: A total of 27 piglets were randomly assigned to three treatment groups (control, infection with Salmonella enterica serover Typhimurium KCTC 2515 (ST) and infection with Escherichia coli KCTC 2571 (EC)) in a completely randomized design to early detection of signs of disease based on body temperature. Totally three inoculations were done consisting of 14 days each and then thermal images were captured to calculate body temperature of pigs at 0, 2, 6, 12, and 24 h and then every 24 h up to 14 days post inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…4 shows different pig diseases detection and ROI tracking using IRT imaging system. Islam et al [52] aimed to explore the early detection of disease signs based on changes in pig body temperature. The researchers conducted three inoculations and monitored the piglet body temperatures at specific intervals: 0, 2, 6, 12, and 24 hours post-inoculation and, subsequently, every 24 hours for a period of up to 14 days.…”
Section: Diseases Detection and Trackingmentioning
confidence: 99%
“…4 shows different pig diseases detection and ROI tracking using IRT imaging system. Islam et al [52] aimed to explore the early detection of disease signs based on changes in pig body temperature. The researchers conducted three inoculations and monitored the piglet body temperatures at specific intervals: 0, 2, 6, 12, and 24 hours post-inoculation and, subsequently, every 24 hours for a period of up to 14 days.…”
Section: Diseases Detection and Trackingmentioning
confidence: 99%
“…Numerous studies have shown that the growth rate is significantly affected if both are not available in the right proportions. Without proper nutrition, the animals can become depressed and are vulnerable to outbursts such as fighting among themselves [12,[102][103][104][105][106][107]. Water and food are interdependent and linearly related; food behavior, especially, depends on water intake [105].…”
Section: Eating and Drinking Solutionsmentioning
confidence: 99%
“…Early disease detection is a practice to reduce the mortality rate through illness or infection. The following incident points out that the disease monitoring process cannot be ignored, especially in the fight against epidemics: in 2018, 200 million pigs were culled due to the swine flu outbreak in China [117,118] and 8 million pigs in Korea [102], which did catastrophic damage to the livestock industry. Disease detection is essential to ensure the health of pigs and prevent epidemics from transferring from pigs to humans.…”
Section: Early Disease Detection At a Farm Levelmentioning
confidence: 99%
See 2 more Smart Citations